1999
DOI: 10.1103/physrevlett.82.4723
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically Reduced Number of Protein Ground State Candidates

Abstract: Geometrical properties of protein ground states are studied using an algebraic approach. It is shown that independent from inter-monomer interactions, the collection of ground state candidates for any folded protein is unexpectedly small: For the case of a two-parameter Hydrophobic-Polar lattice model for $L$-mers, the number of these candidates grows only as $L^2$. Moreover, the space of the interaction parameters of the model breaks up into well-defined domains, each corresponding to one ground state candida… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…These results show some connection to the work of Ejtihadi et al. [20] With a purely geometrical approach, they were able to reduce largely the candidates of structures that can be chosen as the ground states of sequences. They found that for the case of HP protein model the number of ground state candidates grows only as N 2 , N being the sequence length.…”
Section: The Statistical Properties Of Partnumssupporting
confidence: 57%
See 1 more Smart Citation
“…These results show some connection to the work of Ejtihadi et al. [20] With a purely geometrical approach, they were able to reduce largely the candidates of structures that can be chosen as the ground states of sequences. They found that for the case of HP protein model the number of ground state candidates grows only as N 2 , N being the sequence length.…”
Section: The Statistical Properties Of Partnumssupporting
confidence: 57%
“…[18,19,20] In this article we present one way to break the symmetry, to distinguish the compact structures of lattice model without explicitly considering concrete interaction form. However, since only compact structures are considered here, an loose constraint is actually set on interactions: interactions under which compact structures are preferred as ground energy states.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have investigated the effect of the two‐body pairing term in Eq. 5 on designability 35, 42–45. In particular, Shahrezaei and Ejtehadi showed in the case of a two‐letter code that the set of highly designable structures is robust with respect to potential parameters and is largely determined by the structures' geometry 25.…”
Section: Discussionmentioning
confidence: 99%
“…33,52,53 Additional work has shown that some paircontact structures can remain stable and highly designable across an entire range of mixing parameters ␥ M for any twoletter amino-acid alphabet. 54,55 More recently, an analytical, statistical mechanical treatment for calculating the volume of two-letter HP sequence space folding into particular 2D pair-contact structures has been presented by Kussell and Shakhnovich. 56 Upon decomposing structures into various strings of pair-contacts, which in 2D can form either strands or loops, Kussell and Shakhnovich established that highly designable 2D structures for two-letter amino-acid alphabets should have the following properties: ͑1͒ No loops, ͑2͒ a maximum number of twolength strands, and ͑3͒ a minimum number of larger-length strands.…”
Section: Introductionmentioning
confidence: 99%